MORFOFONEMIK BAHASA TALAUD (THE MORPHOPHONEMIC OF TALAUD) - James Edward Lalira (Balai Bahasa Sulawesi Utara, 2016)
The research of Talaud morphophonemics is based on structural linguistic study. This research is motivated by the renewal of Talaud language structure and aims to describe the process, formulate rules and identify types of assimilation morphophonemics in Talaud language.Based on the result of research, three morphophonemics processes have been found namely processes of change, addition, and deletion of phoneme. From the three processes, phonemic changing process always indicates the sound alignmentpattern examined in terms of phonemic homorganic form. This research has also successfully identified the type of morphophonemics assimilation.